Analysis of the Impact of Bullying on the Socio-Emotional Development of Children Aged 5–6 Years at Save The Kids Kindergarten, Banda Aceh City - Bunga Rian lestari; Liza Fidiawati; Miswatul Hasanah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Analysis of the Impact of Bullying on the Social-Emotional Development of Children Aged 5–6 Years at Save The Kids Kindergarten, Banda Aceh City. Undergraduate Thesis. Early Childhood Teacher Education Study Program, Faculty of Teacher Training and Education, Bina Bangsa Getsempena University. Supervisor I: Miswatul Hasanah, M.Pd., Supervisor II: Liza Fidiawati, M.Pd. This study was motivated by the emergence of bullying behavior among early childhood children, which has the potential to hinder their social-emotional development. Bullying among children aged 5–6 years may occur in verbal, physical, and relational forms, affecting children's ability to interact socially and manage their emotions. This study aimed to describe the forms of bullying experienced by children aged 5–6 years, analyze its impact on their social-emotional development, and identify teachers' strategies in preventing and addressing bullying behavior at Save The Kids Kindergarten, Banda Aceh City. This research employed a qualitative approach using a case study design. The research subjects consisted of 23 children in Group B aged 5–6 years and two classroom teachers as informants. Data were collected through observation, interviews, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldana, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The findings revealed that the forms of bullying identified included verbal bullying, such as teasing and giving negative nicknames; physical bullying, such as pushing and taking classmates’ toys; and relational bullying, such as social exclusion and rejection from playgroups. The impact of bullying on children's social development was reflected in difficulties interacting with peers, decreased participation in group activities, and a tendency to withdraw from social environments. The emotional impacts included decreased self-confidence, feelings of sadness and anxiety, frequent crying, and emotional instability. Teachers' strategies for preventing and addressing bullying included monitoring children's interactions, providing guidance and advice, fostering mutual respect, developing empathy, and collaborating with parents. Therefore, bullying has a negative impact on the social-emotional development of young children, highlighting the need for continuous prevention and intervention efforts by both teachers and parents.